Instituições, economia do conhecimento e crescimento econômico : uma análise da evolução recente da economia do Espírito Santo - Caçador, Sávio Bertochi (2024)
This thesis is about the evolution of the institutions of the Espírito Santo’s economy in recent decades, seeking to use extensive literature on the subject in Economic Science to understand facts that marked the institutional turnaround that occurred in the politics and economy of Espírito Santo since 2003, mainly those related to the subsequent evolution in the results of important public policies. It is shown that the institutional development that led to improvements in these policies contributed decisively to the prominence of Espírito Santo in several social indicators, bringing it closer to more developed Brazilian states, but has not yet impacted the indicators of the knowledge and learning economy in the same way, which is problematic for the future of the economy of Espírito Santo, even more so at a time when, unlike in recent decades, the state has grown below the national average (2010s). It is concluded that accelerating the improvement of science, technology and innovation (ST&I) indicators, making the Regional Innovation System (RIS) of Espírito Santo more robust, becomes even more essential than before, based on the construction of a true State policy for these areas. This is fundamental for the state's economy to return to growing above the national average and, consequently, for its social indicators to continue improving in a sustainable way